2018
DOI: 10.1128/msphere.00269-18
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium Genomics Using MinION and Illumina Sequencing Enables Genome Completion and Correction

Abstract: Fusobacterium spp. are Gram-negative, oral bacteria that are increasingly associated with human pathologies as diverse as periodontitis, preterm birth, and colorectal cancer. While a recent surge in F. nucleatum research has increased our understanding of this human pathogen, a lack of complete genomes has hindered the identification and characterization of associated host-pathogen virulence factors. Here we report the first eight complete Fusobacterium genomes sequenced using an Oxford Nanopore MinION and Ill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Many of these proteins are predicted surface adhesins with homology to Fap2, a key protein involved in F. nucleatum-induced colorectal cancer modulation. We subsequently sequenced and completed a total of nine Fusobacterium genomes and previously showed that genes larger than 3 kb had a high error rate, as validated in this study for the T5aSS proteins (29,30,34). A comparison of all annotations of T5aSS to T5dSS autotransporters for strains F. nucleatum 25586 and F. nucleatum 23726 can be found in Table S1 in the supplemental material.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Many of these proteins are predicted surface adhesins with homology to Fap2, a key protein involved in F. nucleatum-induced colorectal cancer modulation. We subsequently sequenced and completed a total of nine Fusobacterium genomes and previously showed that genes larger than 3 kb had a high error rate, as validated in this study for the T5aSS proteins (29,30,34). A comparison of all annotations of T5aSS to T5dSS autotransporters for strains F. nucleatum 25586 and F. nucleatum 23726 can be found in Table S1 in the supplemental material.…”
Section: Resultssupporting
confidence: 54%
“…The reason for this lack of molecular studies in Fusobacterium is its well-known genetic recalcitrance, with only four strains of F. nucleatum yielding chromosomal modification (15,(26)(27)(28). To aid in our understanding of virulence at the genetic and molecular level, we recently completed nine Fusobacterium genomes and created the FusoPortal database that includes detailed genomic and bioinformatic analysis of this emerging pathogen (29,30). These genomes were used here to identify and correct protein families of the autotransporter, FadA, and MORN2 domaincontaining proteins, all of which are predicted to play key roles in cellular binding and invasion.…”
mentioning
confidence: 99%
“…Detailed sequencing statistics and assembly methods are reported in a concurrent publication by Todd and colleagues ( 17 ). Briefly, genomic DNA was isolated from Fusobacterium cultures and sequenced using MinION (Oxford Nanopore Technologies) and Illumina platforms.…”
Section: Methodsmentioning
confidence: 99%
“…All accession numbers for data are provided in Table 1 . In addition, all raw sequencing data have been deposited in the NCBI sequence read archive (SRA) as documented in a companion manuscript accompanying this report ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, due to the limited reading length, the short read-based sequencing approach using the Illumina platform is not optimal for the de novo assembly of whole genome. However, because of the high reading accuracy, this platform is suitable for guided assembly and read mapping combined with long read technology (Oxford Nanopore Technologies, ONT) [21]. The combination of these two platforms creates a robust pipeline, which ensures highly contiguous assembly and high consensus accuracy, making accurate gene identification and characterization possible.…”
Section: Introductionmentioning
confidence: 99%